2015
DOI: 10.4300/jgme-07-01-42
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Wellness and Mental Health Awareness Among Physicians in Training: Perspective of a National, Multispecialty Panel of Residents and Fellows

Abstract: Background Physicians in training are at high risk for depression, and physicians in practice have a substantially elevated risk of suicide compared to the general population. The graduate medical education community is currently mobilizing efforts to improve resident wellness. Objective We sought to provide a trainee perspective on current resources to support resident wellness and resources that need to be developed to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(79 citation statements)
references
References 17 publications
2
76
1
Order By: Relevance
“…The identified trend may reflect the medical community's increased awareness of depression or developments external to medical education. 91 Future studies should explore specific factors that may explain this trend.…”
Section: Discussionmentioning
confidence: 99%
“…The identified trend may reflect the medical community's increased awareness of depression or developments external to medical education. 91 Future studies should explore specific factors that may explain this trend.…”
Section: Discussionmentioning
confidence: 99%
“…51 PHYSICIAN DEPRESSION AND SUICIDE problem is among trainees as the ACGME doesn't collect data on resident suicide (M. Miller, personal communication, June 30, 2013). The ACGME recently convened the Council of Review Committee Residents to study resident wellness and mental health following two resident suicides in 2014, 49 but it is not clear what authority will be given to their recommendations. Finally, we don't know a lot about what works with practicing physicians, because little research has been done.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Using existing literature on well‐being programmes and the Beyond Blue recommendations, our sessions were curated to validate the feelings of those interns who experience medicine as stressful, to promote well‐being, self‐awareness and positive coping strategies and to cultivate a supportive learning and work environment …”
Section: Methodsmentioning
confidence: 99%
“…Doctor well-being is thought to impact professionalism, physical and mental health, career satisfaction, work sustainability and the quality of care delivered to patients. [1][2][3] The tragic loss of Australian young doctors to suicide, the prevalent reports of workplace bullying and harassment in medicine and surgery and the growing body of evidence revealing high rates of psychological distress, burnout and mental illness among doctors all point to the need to promote doctors' well-being and address the cultural factors within medicine that adversely impact doctors' health. [4][5][6][7] The Beyond Blue health report revealed that younger doctors were more adversely affected by poor rates of mental health compared to other health professionals.…”
Section: Introductionmentioning
confidence: 99%